2020
DOI: 10.1074/jbc.ra120.012943
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and mitogenic signals drive interleukin 23 subunit alpha (IL23A) secretion independent of IL12B in intestinal epithelial cells

Abstract: The heterodimeric cytokine interleukin-23 (IL-23 or IL23A/IL12B) is produced by dendritic cells and macrophages and promotes the proinflammatory and regenerative activities of T helper 17 (Th17) and innate lymphoid cells. A recent study has reported that IL-23 is also secreted by lung adenoma cells and generates an inflammatory and immune-suppressed stroma. Here, we observed that proinflammatory tumor necrosis factor (TNF)/NF-κB and mitogen-activated protein kinase (MAPK) signaling strongly induce IL23A expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 59 publications
(89 reference statements)
1
24
0
Order By: Relevance
“…However, recent papers underscore the possibility that the IL-23A-p19 subunit can be secreted as a standalone protein as shown that activated neutrophils and monocytes not only secrete the IL-23 p19/p40 heterodimer in cell supernatants, but also the IL-23A-p19 subunit which was not complexed with EBI3 [ 20 ]. In addition, a recent publication described that epthelial cancer cells could secrete the p19 subunit without being complexed to p40 beta subunit [ 21 ]. A similar situation may be applicable in our cellular system, especially under conditions where the cells highly overexpress the p19 protein after transfection.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent papers underscore the possibility that the IL-23A-p19 subunit can be secreted as a standalone protein as shown that activated neutrophils and monocytes not only secrete the IL-23 p19/p40 heterodimer in cell supernatants, but also the IL-23A-p19 subunit which was not complexed with EBI3 [ 20 ]. In addition, a recent publication described that epthelial cancer cells could secrete the p19 subunit without being complexed to p40 beta subunit [ 21 ]. A similar situation may be applicable in our cellular system, especially under conditions where the cells highly overexpress the p19 protein after transfection.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore measured IL-23, IP-10 (CXCL10), and Hsp60. We chose IL-23 because the transcriptomic analysis revealed that NKG2 a/c + CD8 + T cells expressed high levels of IL23R and because this pro-inflammatory cytokine is known to be expressed in the gut ( Lim et al., 2020 ). IP-10 was selected because it was shown that it is increased in the gut during SIVmac infection ( Ploquin et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the two subunits are expressed together and form the IL23 heterodimer (84), but the gene expression of these two subunits is not always temporally synchronized (85). It is possible that IL23 p19 could have an independent function or an alternative partner in intestinal epithelial cells, as has been suggested recently (86). In contrast to the induction of IL23A, Stx appears to inhibit expression of IFNG and many ISGs such as CXCL11, since these cytokines and downstream factors were downregulated in WT compared to ∆∆stx infected colons.…”
Section: Discussionmentioning
confidence: 96%